BE + -ING est-il un marqueur d’aspect ? - Paul Larreya (Anglophonia)
This paper aims to show that, in all of its uses (including those in which the meaning seems to bear little relation to ‘progressiveness’), BE + -ING expresses a way of viewing the event which may be termed a focusing vision (as opposed to the globalizing vision which characterizes the simple tenses of the English verb), and consists in (so to speak) zooming in on one short moment of the event, usually in order to identify the event itself or one of its characteristics. The point of mental observation (the reference point) may be unique or multiple; in the latter case it may be mobile - it may move over a period of time whose limits are more or less (im)precise.